Carbon‐Based Microbial‐Fuel‐Cell Electrodes: From Conductive Supports to Active Catalysts - Li, Shuang; Cheng, Chong; Thomas, Arne (Advanced materials (Weinheim), 2017)
Microbial fuel cells (MFCs) have attracted considerable interest due to their potential in renewable electrical power generation using the broad diversity of biomass and organic substrates. However, the difficulties in achieving high power densities and commercially affordable electrode materials have limited their industrial applications to date. Carbon materials, which can exhibit a wide range of different morphologies and structures, usually possess physiological activity to interact with microorganisms and are therefore fast‐emerging electrode materials. As the anode, carbon materials can significantly promote interfacial microbial colonization and accelerate the formation of extracellular biofilms, which eventually promotes the electrical power density by providing a conductive microenvironment for extracellular electron transfer. As the cathode, carbon‐based materials can function as catalysts for the oxygen‐reduction reaction, showing satisfying activities and efficiencies nowadays even reaching the performance of Pt catalysts. Here, first, recent advancements on the design of carbon materials for anodes in MFCs are summarized, and the influence of structure and surface functionalization of different types of carbon materials on microorganism immobilization and electrochemical performance is elucidated. Then, synthetic strategies and structures of typical carbon‐based cathodes in MFCs are briefly presented. Furthermore, future applications of carbon‐electrode‐based MFC devices in the energy, environmental, and biological fields are discussed, and the emerging challenges in transferring them from laboratory to industrial scale are described. Carbon‐based electrodes with different morphologies and structures are widely used in microbial fuel cells from conductive supports (anode) to active catalysts (cathode). Recent advancements in the design of carbon materials for anodes (conductivity, biofilm formation, interaction) and cathodes (catalytic activity) are discussed separately. The future perspectives and emerging challenges of this area are also highlighted.